The Knowledge, Service Features, Benefits, And Convenience and Their Influence on Customer Interest: Evidence on BSI Mojopahit 2 Mojokerto City, Indonesia - Mutia Hendarti, Alvina; Candra Yudha, Ana Toni Roby; Wicaksono, Rianto Anugerah; Maksum, Maksum; Huda, Nurul (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2023)
This study investigates the influence of customer knowledge, service features, perceived benefits, and convenience on user interest in adopting BSI Mobile Banking at Mojopahit 2 Branch, Mojokerto City, Indonesia. Using a quantitative approach with a purposive sample of 100 active users, the study employed multiple linear regression analysis through SPSS. Results demonstrate that all four variables significantly affect customer interest, both individually and simultaneously, with perceived benefit emerging as the most dominant factor influencing user adoption. This study contributes to the growing body of research on Islamic digital banking by highlighting how cognitive and experiential factors drive mobile banking adoption in emerging economies with large Muslim populations. Unlike many conventional studies, this research emphasizes the unique feature set of Islamic mobile banking—such as zakah calculators and Qibla direction services—that align with faith-based financial behaviors. The findings provide actionable insights for Islamic financial institutions aiming to expand digital financial inclusion while preserving Shariah compliance. Future international studies can build on this model by comparing adoption dynamics across Islamic banking systems, examining the role of religious values in fintech usability, or integrating behavioral economics into Islamic digital finance frameworks.